(untitled) (Annals of Medical Research, 2021)
Aim: Endometrial carcinoma constitutes the most common gynecological malignancy. Although early diagnosis is important as in all other malignancies, there still exists no screening-imaging modality that can be used effectively in the 517diagnosis of endometrial carcinomas. This study investigated the role of the cervical Papanicolaou (PAP) smear test in the diagnosis of endometrial carcinoma and evaluated the correlation of the results with histological and prognostic data.Material and Methods: Data obtained from 367 patients who underwent hysterectomy and lymph node dissections due to endometrial carcinoma at Gaziantep University Medical Faculty Hospital between 2010 January-2018 June were retrospectively evaluated. PAP smear results of 75 of these patients, who had undergone cervical PAP smear screening preoperatively (in a 1-36 month period), were evaluated independently by two pathologists. The relationship of the results with diagnosis and prognostic data was investigated.Results: Of the 75 cases included in the study; 58 were endometrioid endometrial carcinomas, 9 were serous carcinomas, 6 were malignant mixed Mullerian tumours, 1 was clear cell carcinoma, and 1 was adenosquamous carcinoma. Atypical glandular cells were detected in 29 cases (38.6%). While the evaluation of the relationship of positive cases with histological and prognostic data revealed no relationship with histological tumor type or cervical and lymph node involvement, depth of myometrial invasion presented a significant result.Conclusion: Although rates of endometrial carcinoma detection with PAP smear screening are not very high, they are also not negligible. The detection of an increase in smear positivity rate in correlation with an increase in myometrial invasion depth in our study is quite significant as it represents an important parameter with implications for the surgical procedure.